(untitled) (mathematica didactica, 2021)
Problem solving is an important part of mathematics teaching that is difficult to implement. Therefore, there are several approaches to foster the problem solving competencies of students and teachers. In this paper, another approach at fostering such competencies that so far has received little attention is presented and discussed: Working with multiple solution problems and concrete solution ideas in the form of figures given to the problem solvers. Those figures hint at solutions that need to be elaborated by the problem solvers, fostering the use of heuristics. The method is presented using a geometric problem; results and experiences of tests are discussed.